Notary Legal Responsibility for Notarial Defect Deed in Realizing Legal Certainty - Kamilah Kamilah; Endang Sutrisno (Pelopor Publikasi Akademika, 2026)
Notaries as public officials have the authority to make authentic deeds that function to provide legal certainty for the parties. However, in practice, deeds are still found that are notarially defective due to non-fulfillment of formal provisions as stipulated in Article 44 of the Notary Position Law, which has the potential to cause legal losses. The normative juridical research approach, with the problem of how legal accountability for notaries is related to notarial defect deeds in realizing legal certainty based on Article 44 of the Law on Notary Positions. This study aims to analyze the legal position of deeds that have a notarial defect and the legal liability of the notary to the deed in realizing legal certainty. The results of the study show that violations of the provisions of Article 44 of the Notary Position Law, such as not reading the deed in front of the parties, not fulfilling the presence of witnesses, or not signing at the same time, can cause the deed to experience a notarial defect. The legal consequence that arises is a reduction in the evidentiary power of the deed so that it can be held as a deed under hand or even null and void for the sake of the law. In addition, notaries can be held legally liable in civil cases if proven to have committed mistakes or omissions that cause losses to the parties. Therefore, compliance with the provisions of laws and regulations and the application of the principle of prudence in making deeds are important to realize legal certainty.